Impact of Dollarisation on Exchange Rate Volatility and Rational Choice of Currency Regime: Evidence from two EU Candidate Countries - Malovic, Marko G; Özer, Mustafa; Zdravkovic, Aleksandar (Industrija, 2017)
Objective of this paper is to empirically examine whether widespread unofficial dollarisation plays significant role in determination of exchange rate dynamic in Turkey and Serbia, as one big and one small of the EU candidate countries under managed floating currency regime and synthesize consequent policy recommendations. Our time-series approach utilised monthly data from 2006-2016 to research the aforementioned relationship. After resolving non-stationarity issues, we deployed GARCH analysis to pinpoint the sources of volatility. Our research shows that in Serbia dollarisation has significant and robustly positive influence on exchange rate levels, but not so in Turkey, whose national currency is pretty robust in levels yet its volatility is more sensitive than Serbian dinar to volatility of dollarisation. In addition, Serbian foreign exchange reserves share in the money supply positively influences dinar-euro nominal exchange rate volatility, while Turkish reserves’ share in money supply has negative impact on exchange rate volatility. Even though uncovered interest parity doesn’t hold in either of countries, Serbian dinar is somewhat susceptible to interest rate manipulation, unlike Turkish lira. In the end, one could conclude that flexible exchange rate has more sense and better results in Turkey than in Serbia, but rational choice between earlier -agreed upon or unilateral- official dollarisation on the one hand and continuing with managed (systematic) floating on the other in these two EU candidate countries, requires additional, more precise cost-benefit analysis, as formalised in the discussion and suggested for future research.